Purwarupa dan Kinerja Pengering Gabah Hybrid Solar Heating dan Photovoltaic Heater dengan Sistem Monitoring Suhu - Usman, Usman; Muchtar, Akhyar; Muhammad, Umar; Lestari, Nunik (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2020)
Grain drying is a process to reduce grain moisture content to certain conditions, so the grain can last longer in storage. TheÃ‚Â grainÃ‚Â dryer model used in this research was Indirect Type Solar Dryer (ITSD). In order toÃ‚Â makeÃ‚Â this dryer can work at night,Ã‚Â heating element that used electrical energy from solar panels was added. This energy is a renewable and environmentally friendly energy.Ã‚Â This dryer was equipped with a temperature monitoring system and control of the photovoltaic heater.Ã‚Â The results of temperature monitoring and voltage sensors to controlling photovoltaic heaters based on validation are categorized as work measurement tools, because they have an error of 0.5% Ã¢â‚¬â€œ 2%.Ã‚Â Whereas the relay works when the battery voltage is 11 - 10.9 V. This dryer can dry grain to reach a moisture content of 14.90% from initial Ã‚Â moisture content of 48.46%. The drying process lasts for 11 hours, which is 7 hours using solar energy and 4 hours using photovoltaic heaters. The average temperature produced by dryer system during the drying process is 35.28 Ã‚Â°C with a drying efficiency of 60.14%.